IoT-Based Smart Home Automation System - Shazali, Zhamira Azreen; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2025)
This work presents a smart home automation system using IoT technology to enhance convenience, efficiency, and security. It allows users to control household devices via an IoT app connected to a Wi-Fi network, with data stored in Firebase for real-time synchronization. Key features include automatic lighting controlled by a PIR sensor to save energy and an automatic fan system with a DHT11 sensor that adjusts based on room temperature for comfort. The smart door system uses an RFID reader and servo motor to open/close the door, with an LCD showing its status. An ESP32 camera captures images when the doorbell is pressed, enhancing security. The IoT app enables remote device control via smartphones. EEPROM stores data like Wi-Fi credentials for reconnection after power interruptions. This system demonstrates how IoT can create smarter, energy-efficient homes with automated control, remote monitoring, and efficient data management.